(untitled) (Academia Science Repository, 2023)
Allergies are a very common disease, with about 20% of people in North America and western Europe experiencing pollinosis (allergic rhinoconyuktivitis, allergic rhinitis), according to the Health Ministry. Worldwide, the number of people infected with allergies is increasing. According to M, about 30-40% of people have allergies for part of their lives. Allergic diseases are most common in children, especially when it comes to food allergies .